Understanding Peer Support Work Role Implementation, Work-Life Boundary Navigation and Technological Boundary Transcendence in a Virtual Space - Mirbahaeddin, Elmira (Université d'Ottawa / University of Ottawa, 2024)
As mental health care increasingly embraces recovery principles, the role of peer support workers (PSWs) has gained recognition. The work that mental health PSWs do became particularly important during the COVID-19 pandemic, when increased needs for mental health care became apparent but were often unmet. This article-based doctoral thesis adopts an interdisciplinary perspective that combines research on management and organization with research on health care and systems. The thesis examines the mental health peer support role and its integration within teams, organizations and health systems. It also considers the peer support role as it was enacted in a virtual space, which became a requirement due to pandemic work-from-home mandates. Within the context of the virtual space, PSWs confronted work-life boundaries that they had to navigate as they enacted their work roles. The virtual space also presented technological and social challenges to and opportunities for peer support, which are examined in this thesis from the points of views of PSWs and peers. Overall, this thesis attends to the PSW role more generally, and to peer support work in the specific context of a virtual environment. The thesis is composed of three studies, the second and third of which had to be adapted to the unexpected challenges and opportunities posed by the COVID-19 pandemic. Study 1 (presented in Chapter 2) is a narrative review that synthesizes the literature on factors influencing formal PSW role implementation in mental health systems. The findings are synthesized in a multilevel framework consisting of macro, meso and micro level influences. The analysis reveals that macro-level influences on PSW role implementation include socio-cultural, regulatory, political and economic factors, most of which act as obstacles. At the meso level, organizational culture, leadership, and human resource management policies play a significant role. Micro-level influences center around PSWs' relationships with team members. Interlevel interactions are also discussed. This study is co-authored with Professor Samia Chreim and was published in Administration and Policy in Mental Health and Mental Health Services in February 2022. For Studies 2 and 3, qualitative data were collected from members of a peer support organization situated in Ottawa. This organization is a publicly funded, not-for-profit organization that provides services free of charge to people experiencing mental health and addictions challenges. Due to the pandemic, all services and operations of this organization transitioned to remote services involving virtual platforms. Study 2 (presented in Chapter 3) is a qualitative case study that delves into the work-life boundary challenges and management of PSWs who were providing virtual mental health support during the pandemic. The study identifies temporal, physical, and task-related boundary challenges in work-life domains. Strategies employed by PSWs to manage these boundaries include segmenting and integrating work and personal domains. The study highlights the importance of self-care and the need for training on work-life boundary management for mental health workers. This research is co-authored with Professor Samia Chreim and is published in BMC Public Health. Study 3 (presented in Chapter 4) focuses on the transition from in-person to virtual mental health peer support services. Through semi-structured interviews with PSWs and service users (or peers), the research examines how technological factors act as bridges and boundaries to mental health peer support services, and whether and how a sense of community can be built or maintained among PSWs and peers in a virtual space when connections are mediated by technology. The findings highlight the mental health peer support needs that were (un)met through virtual services, the technology-based boundaries that were manifested and the steps taken to remove some of these boundaries, and the strategies employed by the organization and its members to establish and maintain a sense of community in a virtual environment marked by physical distancing and technology-mediated interrelations. The manuscript pertaining to this study is co-authored with Professor Samia Chreim and will be submitted soon to an academic journal. Overall, this thesis presents a unique and multi-faceted exploration of the implementation of peer support worker roles in mental health systems and their adaptation to virtual environments. It makes a number of contributions. The multilevel framework developed in Study 1 not only advances knowledge in the field but also offers a structured approach for policymakers and organizations to enhance the formal incorporation of PSW roles into mental health systems. Study 2 provides valuable insights into the nature of work-life boundaries in a virtual space, an important topic at a time when peer support workers and organizations are considering whether and how to maintain some form of virtual work post-pandemic. Study 3 adds to knowledge by highlighting the significance of virtual peer support beyond pandemic conditions. It also enhances understanding of the need for technological adaptation in mental health services and for community building regardless of the model of service. Limitations and implications for research, practice and policy are addressed.
Keywords: Boundary Management; Peer Support; Role Implementation; Mental Health; COVID-19 Pandemic; Sense of Community; Work-life Interface; Qualitative Methods; Virtual Work; Role Boundary; Work-life Boundary; Technology Boundary; Access Boundary; Virtual Services; Multilevel Analysis; Narrative Review